THE ROLE OF SELECTED HIGHER EDUCATIONAL INSTITUTIONS (HEIS) AND LOCAL GOVERNMENT UNITS ON INTEGRATING FOOD HERITAGE RESEARCH INTO POLITICAL PRIORITIES: A PUBLIC POLICY ANALYSIS OF LUZON ISLAND, PHILIPPINES - Andalecio, Avi Ben Pestanas (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2021)
The purpose of this study is to show how food heritage, specifically Filipino Pancit, define the culture of their citizens, investigate the efforts of Local Government Units (LGUs), and examine the role of a selected Higher Educational Institution (HEI) as a partner of LGUs in safeguarding food heritage. The researcher used frameworks from international and national cultural agencies and researchers. Observation and in- depth interviews were also used for the documentation process through case study technique, which examined the aspects of statutory control and safeguarding mechanisms to determine the political priorities of involved LGUs and the selected HEI’s role in safeguarding food heritage in the islands of Luzon, Philippines. Findings suggest that LGUs’ sheer political will, knowledge, and awareness on issues on heritage conservation, openness, sustainable practices, and multi-stakeholder participation are essential in robust protection vis-à-vis culture and heritage conservation. This comes with the active participation of stakeholders, especially academic institutions, which provide expertise and extra leg work on research backed by their advocacy rooted on Filipino identity and sustainability to support policies of the government. Ultimately, research-based policymaking is key to open opportunities not just on intangible cultural heritage like Filipino Pancit but on culture and heritage conservation in general.